Building a better mousetrap in the immunologic treatment of acute myeloid leukemia - Reagan, John L.; Fast, Loren D. (Annals of Research Hospitals, 2018)
Sallman et al. report on the successful use of chimeric antigen receptor modified T cells (CAR-T cells) utilizing a Natural Killer Group 2D (NKG2D) target in a patient with acute myeloid leukemia (1).